LUMBAR MICRODISCECTOMY WITH INTRASPINE® – A CASE SERIES - GELDER,CHLOÉ LOUISE (2020)
ABSTRACT Objective To assess postoperative outcomes following lumbar microdiscectomy (LMD) with and without the use of a dynamic intralaminar device IntraSPINE ® . Methods A non-randomized single-surgeon retrospective analysis. Consecutive elective surgery was performed on patients with lumbar disc disease over a 16-month period. The study group was determined by electronic theatre database. Ninety-two (62 LMD and 30 ILD) of the 95 eligible patients were included in the study, with three being excluded due to incomplete data sets. The pain scores were assessed pre- and postoperatively using a 4-point scale (0 – pain free; 1 – mild; 2- moderate; 3 – severe). Results The reduction in postoperative leg pain was similar (LMD 1.9 vs. IntraSPINE® 1.8) but the reduction in postoperative back pain was greater in the IntraSPINE® group (LMD 0.5 vs. IntraSPINE® 1.0; p = 0.17). Early recurrence of disc herniation (< 8 months) was lower in the IntraSPINE® group (6.7% vs. 19.4%; p = 0.097). The need for revision surgery was significantly lower in the IntraSPINE® group (p = 0.015). None of the IntraSPINE® recurrences required revision surgery, compared to 97% of the recurrences in the LMD group. Conclusions This case series raises the possibility that in selected patients, the use of the IntraSPINE® may improve back pain and reduce recurrent disc herniation/revision surgery rates in lumbar microdiscectomy. A prospective randomized trial on the use of the IntraSPINE® should be considered, given the clinical and cost implications of revision surgery. Level of Evidence IV; Case series.